Strategies to Improve Women's Leadership Preparation for Early Career Global Health Professionals: Suggestions from Two Working Groups. Issue 1 (11th July 2022) - Harrison, Meagan; Tran, Dan N.; Pena, Andressa; Iyengar, Sloka; Ahmed Abubakar, Aisha; Hoernke, Katarina; John-Akinola, Yetunde O.; Kiplagat, Sandra; Marconi, Agustina M.; Vaghaiwalla, Tanaz M.; Kalbarczyk, Anna; Weinberg, Jennifer L.
Background: Despite advances in gender equality, women still experience inequitable gaps in global health leadership, and barriers to women's advancement as leaders in global health have been well described in the literature. In 2021, the Johns Hopkins Center for Global Health conducted two virtual working groups for emerging women leaders to share challenges and suggest solutions to advance women's leadership in global health. In this paper, we present emerging themes from the working groups, provide a framework for the results, and discuss strategies for advancing women's leadership in global health. Objectives: The objective of this paper is to synthesize and share the themes of the two working group sessions to provide strategies for improving women's leadership training and opportunities in the field of global health. Methods: Approximately 182 women in the global health field participated in two virtual working group sessions hosted by the Johns Hopkins Center for Global Health using the Zoom platform. Participants were divided into virtual breakout rooms and discussed pre-assigned topics related to women's leadership in global health. The participants then returned to share their ideas in a plenary session. Notes from the breakout rooms and transcripts from the plenary session were analyzed through a participatory and iterative thematic analysis approach. Findings: We found that the working group participants identified two overarching themes that were critical for emerging women leaders to find success in global health leadership. First, the acquisition of individual essential skills is necessary to advance in their careers. Second, the institutional environments should be setup to encourage and enable women to enter and succeed in leadership roles. The participants also shared suggestions for improving women's leadership opportunities such as including the use of virtual technologies to increase training and networking opportunities, intersectionality in mentorship and sponsorship, combatting impostor syndrome, and the importance of work-life balance. Conclusions: Investing in women and their leadership potential has the promise to improve health and wealth at the individual, institutional, and community levels. This manuscript offers lessons and proposes solutions for increasing women's leadership through improving individual level essential skills and fostering environments in which women leaders can emerge and thrive.